Portrayal of Fashion by Turkish & Pakistani Dramas on Major Private TV Channels (Hum TV & Urdu 1) and Viewers Perception - Madni, Abdul Rehman; Abdullah, Mudassar; Hassan, Ali; Nawaz, Tariq (Asian Journal of Empirical Research, 2014)
Dramas generate a great effect on people that influence the segment of society and the whole. This study was designed to identify and estimate the female viewers who belong to Sargodha city watching habits and their perceptions about fashion portray by Hum TV and Urdu 1 dramas. The survey research procedure was adopted. In this study universe is the student (female) of the University of Sargodha, working women and housewives of Sargodha city. Stratified sampling procedure was adopted and for the aim of data collection 300 respondents were stratified on the basis of occupation (students, working women and housewives). After specifying the strata, purposive method of sampling was adopted to gather data. The analytical view of the viewers’ watching habits shows that all the respondents significantly prefer to watch Hum TV than Urdu 1 television channels for watching dramas. Further, it was witnessed that the major portion of the respondents spends more time and pay more attention to the dramas of Hum TV than Urdu 1 dramas. Overall findings illustrate most of the viewers (95%) like Shalwar Qameez. Overall findings further present that 91% respondents do not like female characters with Mini Skirts in Hum TV and Urdu 1 dramas.